The Effect Of Additional Income On Employee Performance Through Workload As An Intervening Variable At The Dairi Regency Inspectorate Office - Heraldo Zinggra; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the effect of Additional Income on Employee Performance by considering the role of Workload as an intervening variable. The research was conducted on employees at the Dairi Regency Inspectorate Office with a sample of 43 employees using the Partial Least Squares (PLS) analysis method. The results show that Workload has a negative and significant influence on Employee Performance, with an Original Sample value of -0.078, T-Statistic of 1,059 < 1.96, and P-Value of 0.000 < 0.05. This means that an increase in Workload tends to decrease Employee Performance. In addition, the results show that Additional Income has a negative influence on Workload, with an Original Sample value of -0.033, T-Statistic of 0.183 < 1.96, and P-Value of 0.856 > 0.05, which shows that the effect of Additional Income on Workload is not significant. The results of the analysis also show that the Additional Income has a positive and significant effect on Employee Performance, with an Original Sample value of 0.891, T-Statistic of 25,845 > 1.96, and P-Value of 0.000 < 0.05, which indicates that the increase in Additional Income can improve Employee Performance. The indirect effect of Additional Income on Employee Performance through Workload was also tested, but the results showed an Original Sample value of 0.003, T-Statistic of 0.132 < 1.96, and P-Value of 0.896 > 0.05, which means that this indirect influence is not significant. Thus, Workload does not play a significant role as a mediator in the relationship between Additional Income and Employee Performance.